Let's make crafts / Inet Gunawan, Desiana Debby, Estu Dyaningtyas; penyunting, Iman Setiadji - INET GUNAWAN; Desiana Debby; Estu Dyaningtyas; Iman Setiadji (Citra Aji Parama, 2008)
iv, 60 hlm. : ilus. ; 22 cm.